2021
DOI: 10.1371/journal.pone.0258473
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for spatial trends in multi-environment diallel analysis in maize breeding

Abstract: Spatial trends represent an obstacle to genetic evaluation in maize breeding. Spatial analyses can correct spatial trends, which allow for an increase in selective accuracy. The objective of this study was to compare the spatial (SPA) and non-spatial (NSPA) models in diallel multi-environment trial analyses in maize breeding. The trials consisted of 78 inter-populational maize hybrids, tested in four environments (E1, E2, E3, and E4), with three replications, under a randomized complete block design. The SPA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Breeders focus on the GEI effect to identify the yield stability of genotypes across different conditions and environments, which cannot be revealed by the separate effects of genotype or environment [ 10 , 11 , 12 , 13 , 14 ]. The GY heritability is exposed to variability across different environments [ 15 , 16 ], which hinders the accuracy of superior varietal selection processes [ 17 ]. Therefore, widely adapted genotypes with the ability to produce stable high yields across diversified environments constitute a major goal for rice breeders.…”
Section: Introductionmentioning
confidence: 99%
“…Breeders focus on the GEI effect to identify the yield stability of genotypes across different conditions and environments, which cannot be revealed by the separate effects of genotype or environment [ 10 , 11 , 12 , 13 , 14 ]. The GY heritability is exposed to variability across different environments [ 15 , 16 ], which hinders the accuracy of superior varietal selection processes [ 17 ]. Therefore, widely adapted genotypes with the ability to produce stable high yields across diversified environments constitute a major goal for rice breeders.…”
Section: Introductionmentioning
confidence: 99%
“…From a broader point of view, the study highlights the importance of maximizing the precision of phenotyping while also maximizing the number of genotypes. While it was not the topic of the study, previous work has shown similar results when comparing advanced experimental designs such as augmented p-rep designs or controlling for spatial variability in the field (Bernardeli et al, 2021;Coelho et al, 2021).…”
Section: Crop Sciencementioning
confidence: 68%
“…It could also be linked to the residual dependence of plots. When spatial trends were taken into account, relevant research on maize [ 36 ], sorghum [ 37 ], barely [ 38 ], potato [ 39 ], and soybean [ 40 ] likewise produced excellent results.…”
Section: Discussionmentioning
confidence: 99%
“…The results of MET data analysis showed that modeling GE interactions with FA models in combination with models for spatial variations resulted in a significant improvement in the estimates of genetic parameters, and this was demonstrated with evidence of heritability. Results from a related study on sorghum [ 41 ], durum wheat [ 42 ], and maize [ 36 ] revealed that modeling field spatial correlation plus MET through FA combined under a linear mixed model also indicated significant improvement in heritability analysis. The FA models were found to be useful not only for estimating and predicting GxE interaction effects, but also for estimating GxE variance and performing bi-plot analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation